Liquid–liquid two‐phase flow in ultrasonic microreactors: Cavitation, emulsification, and mass transfer enhancement. Issue 4 (27th October 2017) - Zhao, Shuainan; Dong, Zhengya; Yao, Chaoqun; Wen, Zhenghui; Chen, Guangwen; Yuan, Quan
Abstract : The effects of ultrasound on the hydrodynamic and mass transfer behaviors of immiscible liquid–liquid two‐phase flow was investigated in a domestic ultrasonic microreactor. Under ultrasonic irradiation, cavitation bubble was generated and underwent violent oscillation. Emulsification of immiscible phases was initiated by virtue of oscillating bubbles shuttling through the water/oil interface. The pressure drop was found to decrease with increasing ultrasound power, with a maximum decrement ratio of 12% obtained at power 30 W. The mass transfer behavior was characterized by extraction of Rhodamine B from water to 1‐octanol. An enhancement factor of 1.3–2.2 on the overall mass‐transfer coefficient was achieved under sonication. The mass transfer performance was comparable to passive microreactor at similar energy dissipation rate (61–184 W/kg). The extraction equilibrium was reached under a total flow velocity 0.01 m/s and input power 20 and 30 W, exhibiting its potential use in liquid‐liquid extraction process. © 2017 American Institute of Chemical Engineers AIChE J, 64: 1412–1423, 2018